PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING PADA MEDIA SOSIAL INSTAGRAM - Siregar, Stephanie Gebiela; Simajuntak, Jontro (SCIENTIA JOURNAL, 2021)
This research aims to analyze and determine how the influence of celebrity endorsers and brand image on purchasing decisions of Scarlett Whitening on Instagram social media. The data collection technique in this study was the distribution of questionnaires with purposive sampling method with a sample of 270 respondents who were determined by the Isaac and Michael formula. The data from the questionnaires were processed using SPSS version 25. The results showed that t test celebrity endorser > t table, that is 7.309 > 1.969 and a significant value of 0.000 <0.05. This shows that celebrity endorsers have a positive and significant effect on the purchase decision of Scarlett Whitening on Instagram social media. Then t test of brand image > t table, that is 24.014> 1.969 with a significant value of 0.000 < 0.05. This shows that brand image has a positive and significant effect on the purchase decision of Scarlett Whitening on Instagram social media. Furthermore, celebrity endorser and brand image together have a positive and significant effect on purchasing decisions. Evidenced by the results of the F test with the value of F test is 397.920 > 2.64 F table. With a significant value of 0.000 <0.05.Keywords: Celebrity Endorser; Brand Image; Buying decision.